(untitled) (Bangladesh Journal of Medical Microbiology, 2010)
This study was carried out to isolate M. tuberculosis from smear positive sputum samples by MB/BacT automated culture system and investigate the drug resistance pattern. Among 101 smear positive cases 96 (95.05 %) yielded growth of Mycobacteria, 3 (02.97 %) were contaminated and 2 (01.98 %) showed no growth. Culture positive detection time for M. tuberculosis was lowest 7 days and highest 36.3 days and average detection time was11.3 days. Detection time for NTM was 19.2 days. Among 96 isolates 95 (98.96 %) were M. tuberculosis and remaining 1 (1.04 %) was photochromogen Non-tuberculous Mycobacteria (NTM). Out of 95 M. tuberculosis 51 (53.84 %) were resistant to at least one drug, 38 (40.00 %) to INH, 31 (32.63%) to RMP, 13(13.68 %) to SM, 11 (11.58 %) to EMB and 10 (10.53 %) to PZA and multi-drug resistant tuberculosis (MDR-TB) was 21 (22.11 %). Resistance to one drug was 21 (22.11%), two drugs 15 (15.79 %), to three drugs 10 (10.53 %) and resistant to four or more drugs 5(5.26 %) cases. Bangladesh J Med Microbiol 2010; 03 (02): 13-17